Expansion and preferential activation of the CD14+CD16+ monocyte subset during multiple sclerosis. Issue 6 (18th March 2014) - Chuluundorj, Delgertsetseg; Harding, Scott A; Abernethy, David; La Flamme, Anne Camille
Abstract : Multiple sclerosis (MS) is an immune‐driven, demyelinating disease of the central nervous system (CNS). Although many types of immune cells are involved in disease progression, activated monocytes are believed to be one of the first to arrive to the brain and initiate inflammation. However, little is known about how the two main monocyte subsets, CD14 ++ CD16 − and CD14 + CD16 +, are involved in MS. To understand how the phenotype and responses of these monocyte subsets are altered during MS, total monocytes and the purified monocyte subsets from healthy subjects ( n =29) and MS patients ( n =20) were characterized ex vivo and stimulated in vitro with lipopolysaccharide (LPS). The ex vivo analyses showed that total monocytes from MS patients had significantly elevated levels of CD40, CD86, HLA‐DR, CD64 and C‐C motif chemokine receptor 2 (CCR2), and this elevation was most marked on CD16 + monocytes. In vitro stimulation with LPS led to an increase in CD86, HLA‐DR, CD64 and IL‐6 production by monocytes from MS patients. Furthermore, in purified cultures, CD14 + monocytes were found to be the main producers of IL‐10 while CD16 + monocytes produced more IL‐12. In monocytes from MS patients, both subsets produced substantially more IL‐6, and the production of IL‐10 by the CD16 + subset was also significantly elevated compared with healthy monocytes. Together these findings highlight the important contribution of the CD16 + monocyte subset in driving inflammatory responses during MS.